Influence of cerium on solidification, recrystallization and strengthening of Cu-Ag alloys - 常丽丽 贾彬 李胜利 朱新德 冯锐 尚兴军 (Journal of rare earths, 2017)
Cu-Ag-RE alloys with different Ce contents were prepared by vacuum melting, and microstructure evolution and mechanical properties of Cu-Ag-Ce alloys were investigated by optical microscopy, scanning electronic microscopy with electron back-scattered diffraction and tensile test. The results indicated that a columnar to equiaxed transition in cast Cu-Ag-RE alloys was observed due to Ce addition and area of the region with equiaxed grains enlarged with increasing Ce content. Cold-rolled Cu-Ag-RE alloys in annealed condition exhibited a partially or fully recrystallized grain structure depending on the concentration of Ce. The average grain size decreased and texture components changed with increasing Ce content. The main brass-type texture component changed to be copper-type as the Ce content increased from 0.05 wt.% to 1.0 wt.%. The Cu-Ag-RE alloy with 0.2 wt.% Ce showed maximum ultimate tensile strength, while the sample with 1.0 wt.% Ce showed a better comprehensive mechanical property.